2022
DOI: 10.2298/tsci211023015j
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of open micro-channel heat sink with pin fins by multi-objective genetic algorithm

Abstract: Microchannel heat sink is an effective way to solve the heat dissipation problem of electronic devices because of its compact structure and outstanding heat dissipation ability. In order to obtain the high efficiency and low resistance microchannel heat sink , a new structure of open rectangular microchannel heat sink with pin fins was proposed to enhance heat transfer. The orthogonal test method was used to design the experiment, and the three-dimensional software Solidworks was used to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Te orthogonal test is an experimental design method that uses orthogonal tables to arrange experiments and perform multifactor and multilevel data analysis [27]. In this article, the purpose of the orthogonal test is to investigate the infuence of geometric parameters of the disk magnetic coupler on maximum magnetic torque and eddy current loss.…”
Section: Determinations Of Orthogonal Test Factors and Levelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Te orthogonal test is an experimental design method that uses orthogonal tables to arrange experiments and perform multifactor and multilevel data analysis [27]. In this article, the purpose of the orthogonal test is to investigate the infuence of geometric parameters of the disk magnetic coupler on maximum magnetic torque and eddy current loss.…”
Section: Determinations Of Orthogonal Test Factors and Levelsmentioning
confidence: 99%
“…Model Formation. Te response surface approximation was performed to obtain the ftting polynomial function between the objective functions and the design variables [27]. Te response surface approximation model is a secondorder model, which has an intercept term, a linear term, a square term, and a quadratic interaction term [27,28]:…”
Section: Optimization Of Disk Magnetic Coupler Based On Genetic Algor...mentioning
confidence: 99%
See 2 more Smart Citations
“…A similar approach has been adopted by Wang et al [121]. Jiang and Pan [122] used the orthogonal test, NSGA-II, and k-mean clustering methods for multi-objective optimization of rectangular fins. Their results showed that a non-uniform fin array with higher pin heights (at the second and fourth row) and thinner fin thicknesses (along the direction of flow) could reduce the thermal resistance of the heat sink.…”
Section: Fin-shape and Arrangement Optimization For Pin-fin Heat Sinksmentioning
confidence: 99%